Obtenção de proteases de Penicillium candidum e seu emprego no preparo de hidrolisados de soro de leite com baixo teor de fenilalanina - Raquel Campos Santos (2005)
Whey, a sub product of high nutritive value, but underused, was used as a substrate to obtain hydrolysates with low phenylalanine contents, to a development of food supplements to phenylketonurians. The enzymatic preparation was achieved from a strain of Penicillium candidum, mould already used in cheese ripening. The cultivate conditions and obtaining of enzymatic preparation was optimized and the partial purification was carried out by precipitation with two volumes of ethanol at 4°C. Three relations enzyme: substrate and three hydrolysis temperature were tested. The hydrolysates were treated with activated carbon column to remove the Phe. The high removal percentages, of 90% to 93%, were obtained with 40°C and 50°C temperatures. No relation with the E:S used was observed.